The effect of teacher self-efficacy, teacher resilience, and emotion regulation on teacher burnout: a mediation model - Li, Shanshan (Frontiers in Psychology, 2023)
Introduction This research aimed to explore the relationships among teacher self-efficacy, teacher resilience, emotion regulation, and teacher burnout within the context of Chinese English as a foreign language (EFL) teachers. Methods A sample of 638 Chinese EFL teachers participated in this study. They completed self-report assessments for teacher self-efficacy, teacher resilience, emotion regulation, and teacher burnout. Confirmatory factor analysis was conducted to establish the construct validity of the measurement tools. Subsequently, structural equation modeling was utilized to assess the proposed structural model. Results The results of the study revealed significant insights. Teacher self-efficacy and resilience exhibited direct and negative associations with teacher burnout. Additionally, an interesting finding emerged where teacher emotion regulation indirectly affected teacher burnout, mediated by teacher resilience. The analysis supported the suitability of the partial mediation model as the best-fit representation of the relationships. Discussion The findings of this study provide valuable implications for EFL teaching programs. The negative connections between teacher self-efficacy, resilience, and burnout highlight the importance of nurturing these factors to mitigate burnout risk. The discovered mediation effect of teacher resilience emphasizes the role of emotion regulation in promoting teachers’ overall well-being. These outcomes collectively contribute to the understanding of teacher dynamics and suggest potential avenues for targeted interventions.